The role of adipose tissue cell elements in the regulation of the nitroxidergic system and possible ways of pharmacological modulation - I. F. Bielenichev; S. O. Maslennikov; N. V. Dobrelia; O. S. Khromov; M. L. Holovakha; V. P. Ryzhenko; O. O. Brek (Сучасні медичні технології)
Endothelial dysfunction is characterized by a decrease in the bioavailability of the vasodilator – nitric oxide (NO), and an increase in the level of vasoconstrictor substances. This imbalance leads to vasoconstriction, leukocyte attachment and inflammatory reactions in the vascular wall, atherosclerosis and thrombosis.